3D bioassembly of cell-instructive chondrogenic and osteogenic hydrogel microspheres containing allogeneic stem cells for hybrid biofabrication of osteochondral constructs. (1st July 2022) - Cui, Xiaolin; Alcala-Orozco, Cesar R; Baer, Kenzie; Li, Jun; Murphy, Caroline A; Durham, Mitch; Lindberg, Gabriella; Hooper, Gary J; Lim, Khoon S; Woodfield, Tim B F
Abstract: Recently developed modular bioassembly techniques hold tremendous potential in tissue engineering and regenerative medicine, due to their ability to recreate the complex microarchitecture of native tissue. Here, we developed a novel approach to fabricate hybrid tissue-engineered constructs adopting high-throughput microfluidic and 3D bioassembly strategies. Osteochondral tissue fabrication was adopted as an example in this study, because of the challenges in fabricating load bearing osteochondral tissue constructs with phenotypically distinct zonal architecture. By developing cell-instructive chondrogenic and osteogenic bioink microsphere modules in high-throughput, together with precise manipulation of the 3D bioassembly process, we successfully fabricated hybrid engineered osteochondral tissue in vitro with integrated but distinct cartilage and bone layers. Furthermore, by encapsulating allogeneic umbilical cord blood-derived mesenchymal stromal cells, and demonstrating chondrogenic and osteogenic differentiation, the hybrid biofabrication of hydrogel microspheres in this 3D bioassembly model offers potential for an off-the-shelf, single-surgery strategy for osteochondral tissue repair.